Role of antimicrobial peptide DEFB126 mutation in pathogenesis of male idiopathic infertility - E. M. Khasanova; L. V. Gankovskaya; V. V. Burmakina (Медицинская иммунология, 2021)
Male infertility is a multifactorial disease, and elucidation of etiopathogenetic mechanisms of its progression is a topical issue. High percentage of the “idiopathic infertility” diagnosis is largely cased by inability to establish etiology of decrease in reproductive spermatic function. Mutation of в-defensin DEFB126 gene is supposed to affect the fertilizing ability of spermatozoa at different levels: it may decrease their ability to migrate through the cervical mucus and reduce binding capacity to epithelial layer of upper female reproductive tract, and it may also increase susceptibility for infections of reproductive tract, due to impairment of local protective function of defensins. Thus, the aim of the present study was to examine possible role of rs11468374 gene polymorphism of the DEFB126 gene in pathogenesis of male idiopathic infertility. Patients and methods: The group of patient with decreased fertility included 54 male subjects, ages 34 to 42, with a control group of 19 ejaculate donors without acute or chronic disease aged 28 to 36. The indicators of sperm motility in the Moscow population were compared with individual levels of DEFB126 gene expression, as well as with estimated distribution frequency of rs11468374 alleles and genotypes among the subjects.As compared with the control group, the infertile patients exhibited a more than seven-fold reduction of DEFB126 gene expression. Analysis of distribution frequency for alleles and genotypes rs11468374 polymorphic marker of the DEFB126 gene revealed that the mutant allele is detected almost twice as often in males with infertility, as compared with control group. No cases with the DEFB126 del/del genotype were found among the control group, in contrary to 16.1% in the group of patients. The patients with DEFB126 del/del genotype exhibited 5.2-fold reduction of sperm motility. Thus, the data obtained may be used to extend our knowledge on the pathogenetic mechanisms of male idiopathic infertility and to improve techniques for its diagnostics, as well as to provide personalized approach to the treatment of male reproductive disorders. The association between carriage of del mutant allele and decreased level of sperm motility suggests a role of this polymorphism in pathogenesis of male infertility. A general decrease in the level of DEFB126 gene expression in the patients affected by infertility also presumes a contribution of defensin 126 to pathogenesis of the disorder.